THERMAL ANALYSIS OF AN OCTAGONAL SHELL EARTH ORBITING BODY (Journal of Engineering, 2005)
The thermal behavior of an octagonal shell orbiting body in space environments had been simulated theoretically in the present work, and a simplified experimental test in a thermal vacuum chamber was also made on half-scale model of the prototype to investigate the problem. A mathematical model was built and simulated numerically by using lumped system technique and finite difference control volsme approach with explicit scheme. The body in its orbit around the earth is assumed to receive solar, albedo and earth radiation heat fluxes. The orbit is circular of (500-Km) height and (40) inclination. The developed computational algorithm is capable of calculating the heat fluxes on body faces and the temperature distribution of the body at any time instant. The results showed that the albedo and earth heat fluxes are smaller when the orbit is higher. In the side faces, the heat fluxes are maximum when orbit inclination is minimum, and vice versa, the inverse behavior is true for the upper and lower faces. The heat fluxes are maximum in winter solstice and minimum in summer solstice. If the difference between the emissivity and absorptivity values is low, the body reaches to synchronous steady state faster. The emissivity is affected more than absorptivity. The temperatures of faces, which see the carth, are more fluctuated than the other faces. Comparison between theoretical and experimental results showed good agreement.